Re-evaluating the burden of rabies in Africa and Asia - Knobel, D.L.; Cleaveland, S.; Coleman, P.G.; Fèvre, Eric M.; Meltzer, M.I.; Miranda, M.E. (FapUNIFESP, 2005)
OBJECTIVE: To quantify the public health and economic burden of endemic canine rabies in Africa and Asia. METHODS: Data from these regions were applied to a set of linked epidemiological and economic models. The human population at risk from endemic canine rabies was predicted using data on dog density, and human rabies deaths were estimated using a series of probability steps to determine the likelihood of clinical rabies developing in a person after being bitten by a dog suspected of having rabies. Model outputs on mortality and morbidity associated with rabies were used to calculate an improved disability-adjusted life year (DALY) score for the disease. The total societal cost incurred by the disease is presented. FINDINGS: Human mortality from endemic canine rabies was estimated to be 55 000 deaths per year (90% confidence interval (CI) = 24 000-93 000). Deaths due to rabies are responsible for 1.74 million DALYs lost each year (90% CI = 0.75-2.93). An additional 0.04 million DALYs are lost through morbidity and mortality following side-effects of nerve-tissue vaccines. The estimated annual cost of rabies is USD 583.5 million (90% CI = USD 540.1-626.3 million). Patient-borne costs for post-exposure treatment form the bulk of expenditure, accounting for nearly half the total costs of rabies. CONCLUSION: Rabies remains an important yet neglected disease in Africa and Asia. Disparities in the affordability and accessibility of post-exposure treatment and risks of exposure to rabid dogs result in a skewed distribution of the disease burden across society, with the major impact falling on those living in poor rural communities, in particular children.